Belo Horizonte: percebendo a cidade a partir da vegetação urbana - Bárbara Rodrigues dos Santos Paes (2022)
As a result of the urbanization process, natural vegetation has been one of the most impacted environmental components, with loss of coverage and alteration of structure and floristic composition, isolated in fragments within the urban area. Biodiversity in urban planning offers differentiated treatments through power relations, which result in a specific distribution of environmental attributes and natural resources. In this context, the research evaluated the density of vegetation cover in the municipality of Belo Horizonte between the years 1984 and 2021, using the Normalized Difference Vegetation Index (NDVI), in order to assess its dynamics in the city's urbanization process. The data demonstrate a significant loss of vegetation throughout the municipality, occurring spatially and unevenly within the intra-urban territory, with protected green areas playing a fundamental role in maintaining vegetation over the analyzed period. Based on the premise that internal inequalities within cities are expressions of physical and environmental changes in flows and socio-environmental practices, and dependent on historical, cultural, political, or economic conditions, this article aims to evaluate whether social and economic aspects influence the spatial distribution of vegetation density in the city of Belo Horizonte, Minas Gerais. The vegetation density was estimated using the NDVI (Normalized Difference Vegetation Index) from Landsat 5 imagery for the year 2010 and analyzed using Global Moran's I and Local Indicators of Spatial Association (LISA), demonstrating that vegetation occurs with a spatially and unevenly extending effect within the intra-urban territory. The vegetation data were also correlated using Geographically Weighted Regression (GWR) analysis with social and economic data from the IBGE census (2010). The results demonstrate that the socioeconomic reality explains part of the observed vegetation variability. GWR analyses show significant values (R2 greater than 0.70) occurring throughout the intra-urban area, but heterogeneously, without a general explanation that applies to the entire municipality, suggesting place-scale effects or neighborhood effects. The findings contribute to discussions on the relationship between vegetation density and models of compact and dispersed cities, hierarchies of social and racial inequality, urban agriculture, and street tree planting, demonstrating the complexity of the environmental relationship in urban area, reflected in the attribute of vegetation.